FKBP51 employs both scaffold and isomerase functions to promote NF-κB activation in melanoma. Issue 14 (22nd June 2015) - Romano, Simona; Xiao, Yichuan; Nakaya, Mako; D'Angelillo, Anna; Chang, Mikyoung; Jin, Jin; Hausch, Felix; Masullo, Mariorosario; Feng, Xixi; Romano, Maria Fiammetta; Sun, Shao-Cong
Abstract: Melanoma is the most aggressive skin cancer; its prognosis, particularly in advanced stages, is disappointing largely due to the resistance to conventional anticancer treatments and high metastatic potential. NF-κB constitutive activation is a major factor for the apoptosis resistance of melanoma. Several studies suggest a role for the immunophilin FKBP51 in NF-κB activation, but the underlying mechanism is still unknown. In the present study, we demonstrate that FKBP51 physically interacts with IKK subunits, and facilitates IKK complex assembly. FKBP51-knockdown inhibits the binding of IKKγ to the IKK catalytic subunits, IKK-α and -β, and attenuates the IKK catalytic activity. Using FK506, an inhibitor of the FKBP51 isomerase activity, we found that the IKK-regulatory role of FKBP51 involves both its scaffold function and its isomerase activity. Moreover, FKBP51 also interacts with TRAF2, an upstream mediator of IKK activation. Interestingly, both FKBP51 TPR and PPIase domains are required for its interaction with TRAF2 and IKKγ, whereas only the TPR domain is involved in interactions with IKKα and β. Collectively, these results suggest that FKBP51 promotes NF-κB activation by serving as an IKK scaffold as well as an isomerase. Our findings have profound implications for designing novel melanoma therapies based on modulation of FKBP51.